2021
DOI: 10.3389/fsurg.2021.721143
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Density and Distribution of Cajal Like Cells Associated With the Pathogenesis of Ureteropelvic Junction Obstruction: A Systematic Review and Meta-Analysis

Abstract: Introduction: Cajal like cells (CLCs) in the upper urinary tract have an ability to generate coordinated spontaneous action potentials and are hypothesized to help propel urine from renal pelvis into the ureter. The objective of this review was to describe the variations in the density and distribution of CLCs associated with ureteropelvic junction obstruction (UPJO).Materials and Methods: Studies comparing the density and distribution of CLCs in the human upper urinary tract in patients with UPJO and healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 61 publications
(115 reference statements)
0
13
0
Order By: Relevance
“…[2]). Based on a recent meta‐analysis, we inferred that a reduced CLC density could be linked to PUJO [2]. Nonetheless, we also showed that CLC density increases with age in healthy subjects, therefore, a lack of strict age matching of cases and controls may have confounded previous reports [2].…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…[2]). Based on a recent meta‐analysis, we inferred that a reduced CLC density could be linked to PUJO [2]. Nonetheless, we also showed that CLC density increases with age in healthy subjects, therefore, a lack of strict age matching of cases and controls may have confounded previous reports [2].…”
Section: Figmentioning
confidence: 99%
“…The density of CLCs has been presumed to be implicated in the pathogenesis of primary pelvi-ureteric junction obstruction (PUJO). Several observational studies have shown that a low density of CLCs is associated with primary PUJO, while other studies failed to demonstrate this (reviewed in Samaranayake et al [2]). Based on a recent meta-analysis, we inferred that a reduced CLC density could be linked to PUJO [2].…”
Section: Morphometric Variations Of Cajal-like Cells Are Associated W...mentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted an immunohistochemical analysis coupled with an advanced image segmentation approach to identify c-Kit expressing CLCs [2]. The results of the analysis are reported as mean (AE SD).…”
mentioning
confidence: 99%
“…PUJO may arise due to intrinsic, extrinsic, or functional factors. Functional obstruction of PUJO could arise due to the impairment of pacemaker potentials of Cajal‐like cells (CLCs) located at the PUJ [1]. These specialised cells play a crucial role in regulating smooth muscle contractions, while contributing to mechanosensory functions.…”
mentioning
confidence: 99%